2003
DOI: 10.1149/1.1554914
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Potential on the Passive Corrosion Properties of Alloys C22 and C276

Abstract: Potentiostatic polarization experiments were performed as a function of potential ͑200 to 700 mV Ag/AgCl ͒ and temperature ͑25-85°C͒ on the Ni-Cr-Mo alloys C22 and C276. X-ray photoelectron spectroscopy ͑XPS͒ and time-of-flight secondary ion mass spectrometry ͑TOF SIMS͒ were used to determine the chemical composition and thickness of the films formed. The currents recorded as a function of applied potential were due to dissolution, with only minor increases in film thicknesses observed. Measured currents for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
78
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 30 publications
7
78
1
Order By: Relevance
“…It has been demonstrated previously [41][42][43] that the PDM can readily explain the observations of the passive state on Alloy-22. Characterization work 41,[44][45][46] has demonstrated that the passive film on Alloy-22 has a distinct layered structure with the inner layer primarily comprising Cr(III) oxide, so it is assumed in the optimization that point defective Cr 2 O 3 is the principal composition of the barrier layer. Fig.…”
Section: Results and Analysis By Numerical Optimizationmentioning
confidence: 77%
“…It has been demonstrated previously [41][42][43] that the PDM can readily explain the observations of the passive state on Alloy-22. Characterization work 41,[44][45][46] has demonstrated that the passive film on Alloy-22 has a distinct layered structure with the inner layer primarily comprising Cr(III) oxide, so it is assumed in the optimization that point defective Cr 2 O 3 is the principal composition of the barrier layer. Fig.…”
Section: Results and Analysis By Numerical Optimizationmentioning
confidence: 77%
“…In a study comparing Alloy 625 to Alloy 276, Lillard [6] found that Alloy 276 had a lower passive current density, and was less susceptible to pitting. In a study on Alloy 276 and Alloy 22, Lloyd et al [24] found that Alloy 22 had a lower passive current density, and was less susceptible to pitting as well. This matches the theory regarding the passive current density; although, when comparing the components of the alloys, Alloy 276 has more Mo than both Alloy 22 and 625, and Alloy 625 has as much Cr as Alloy 22 and 6% more than Alloy 276.…”
Section: Discussionmentioning
confidence: 99%
“…A wide array of in-situ and ex-situ analytical techniques [1][2][3][4][5][6][7][8] has been employed to assess passive behavior and its influence on the corrosion performance of these alloys. The combination of high Cr and Mo contents leads to the formation of a Cr-dominated passive oxide film 2,3,[9][10][11] with a duplex film structure, 12 which provides resistance against oxidizing environments. 13 The nature and composition of these oxide films depend on alloy composition, potential, pH, temperature, and the composition of the environment in which they are formed.…”
mentioning
confidence: 99%